Cervical Artery Dissection and Sports - Engelter, Stefan T.; Traenka, Christopher; Grond-Ginsbach, Caspar; Brandt, Tobias; Hakimi, Maani; Worrall, Bradford B.; Debette, Stephanie; Pezzini, Alessandro; Leys, Didier; Tatlisumak, Turgut; Nolte, Christian H.; Lyrer, Philippe (Frontiers in Neurology, 2021)
Cervical artery dissection (CeAD) occurring in the context of sports is a matter of concern for CeAD-patients. They seek advice on the role of sports in CeAD, and on the safety of resuming sports after CeAD. The scarcity of studies and guidelines addressing these issues poses a challenge. We aimed at summarizing the current knowledge about CeAD and sports in order to provide an informed, comprehensive opinion for councelling CeAD-patients. We took into account pathophysiological considerations, observations of cases reports, series, and registries, and conclusions by analogy from aortic dissection or inherited connective tissue syndromes. In summary, practicing active sports as the cause of CeAD seems uncommon. It seems recommendable to refrain from any kind of sports activities for at least 1 month, which can be extended in case of an unfavorable clinical or neurovascular course. We recommend starting with sport activities at low intensity - preferably with types of endurance sports - and to gradually increase the pace in an invidually tailored manner taking into circumstances of the occurrences of the CeAD in the individual patient (particularly in relation to sports), the meaning of sports activities for the individual well-being, the presence or absence of co-morbidities, of neurological sequela, neurovascular findings, and whether or not there are signs of an underlying connective tissue alteration. Major limitations and several forms of bias are acknowleged. Still, in the absence of any better data, the summarized observations and considerations might help clinicians in advising and counselling patients with CeAD in clinical practice.